PEMANFAATAN EKSTRAK DAUN SIRSAK (Annona muricata L.) DALAM MENINGKATKAN UMUR SIMPAN DODOL - Prawitasari, Ni Made; Suter, I Ketut; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA, 2017)
The soursop leaves are contain antioxidants and antimicrobials to prevent the oxidation and growing fungi of food products made from oils or fats . This study aims to determine the effect of the concentration of soursop leaf extracts to shelf life, activity of water, and sensory properties of dodol and to determine the best concentration of soursop leaves in increasing the shelf life of dodol. The experimental design used in this study was completely randomized design, with 6 levels of soursop leaf extract concentration which consists of 0%, 0.2%, 0.4%, 0.6%, 0.8%, and 1%. The whole treatment was repeated three times to obtain 18 experiment units. Data were analyzed by analysis of variance, and if there was a treatment effect on the observed parameters, then followed by Duncan Multiple Range Test . The results showed that the treatment soursop leaf extract significantly effected (p<0,01) on water activity, aroma, color, taste, overall acceptance, and shelf life, while not significantly effected on texture (P>0,05). Best results was obtained on 0.2% soursop leaf extract with characteristics of dodol were shelf life of 9 days, 0.904 activity of water, 4.27 (like) colors, 4.20 (like) aroma, 3.87 (like) flavor, 3.73 (like) textures, and 3.93 (like) overall acceptance.
Keywords: soursop leaf extract, dodol, shelf life